EKSEKUSI OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Wiwin Dwi Ratna Febriyanti (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
Fiduciary guarantees have existed in society since the Dutch colonial era because the fl exibility of objects that can be imposed by fi duciary increases the need for legal certainty for the guarantee of this model. UUJF requires the registration of fi duciary security to be imposed. Registration is carried out at the Ministry of Law and Human Rights to obtain a fi duciary certifi cate. The fi duciary certifi cate contains irah-irah which the power of execution so that the execution can be carried out immediately without going through a court and is final as explained in article 15 paragraph (2). In practice, this article often becomes a polemic in the community, causing actions against the law and even criminal acts when the fi duciary recipient wants to execute fi duciary collateral. After the decision of the Constitutional Court Number 18/PUU-XVII/2019, in its decision to redefi ne article 15 paragraph (2) and paragraph (3) UUJF, Based on this, this research discusses the executive power of the fi duciary security certifi cate after The Constitutional Court decision Number 18/PUU-XVII/2019. With statutory approach, and a conceptual approach, the conclusion is that the power of execution title in the fi duciary guarantee certifi cate is not changed, it’s just a legal consequence arising from the Constitutional Court decision number 18/PUU-XVII/2019, namely the implementation mechanism for the execution of the fi duciary guarantee certifi cate is carried out the same as the execution of court decisions that have permanent legal force (inkrah), when the grantor of fi duciary does not voluntarily surrender the object of fi duciary security under his control. Apart from that, it must be agreed by the parties regarding breach of contract. breach of contract should be detailed in the main agreement and the imposition of fi duciary security.